High-efficiency, low-crosstalk multiplexed volume Bragg grating for non-mechanical angular magnification. (February 2023) - Han, Yuxing; Hao, Wang; Dong, Yuanzhi; He, Dongbing; Cao, Hongchao; Kong, Fanyu; Jin, Yunxia; Shao, Jianda
Graphical abstract: Highlights: A crosstalk criterion first proposed to evaluate the channel crosstalk quantitatively. Reducing the half-width at first zero (HWFZ) of multiplexed volume Bragg grating (TVBG) to minimize the channel crosstalk. Two 6-channel single TVBGs and a 12-channel cascaded TVBG for ±45° non-mechanical angular magnification. Maximum HWFZ reduced from 12.3496 to 1.7628 mrad; average relative diffraction efficiency of all optimized TVBGs reached 92 %. Abstract: The demand for compact transmitting volume Bragg gratings (TVBGs) for non-mechanical angular magnification is growing quickly in the industrial and defense areas. However, channel crosstalk limits the angular width and diffraction efficiency of multiplexed TVBGs. In this work, a crosstalk criterion is first proposed to evaluate the channel crosstalk quantitatively. Based on this criterion, for ±45° non-mechanical angular magnification, 12-channel high-efficiency low-crosstalk TVBGs are achieved by reducing the half-width at first zero (HWFZ) of the angular selectivity curve. Compared to the unoptimized scheme, the measured average relative diffraction efficiency of all optimized TVBGs reach 92 %, and the maximum HWFZ is reduced from 12.3496 to 1.7628 mrad. Our approach paves the way to develop high-performance multiplexed devices.